PENGARUH FAKTOR FUNDAMENTAL DAN MAKRO EKONOMI TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI PROPERTI DI BURSA EFEK INDONESIA - Meilin Veronica; Reny Aziatul Pebriani (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2020)
The Influence of Fundamental and Macro Economic Factors on The Stock Price in Industrial Property Companies in The Indonesia Stock Exchange. The objective of this research is to empirically prove the influence of return on equity, debt to equity ratio, net profit margin, inflation, rate and interest rate Simultaneously and Partially on the stock price. The object of this research are 18 industrial property companies listed on the Indonesia Stock Exchange of research period of 2015 to 2018. The analytical method used is Multiple Linear Regression. The result of this research simultaneously indicates that return on equity, debt to equity ratio, net profit margin, inflation, rate, and interest rate influence the stock price. The research conducted partially indicates that net profit margin significantly influences the stock price. Return on equity, debt to equity ratio, inflation, rate, and interest rate do not influence the stock price.